Blood pressure and intra-ocular pressure in a sample of young professional footballers in Benin City, Nigeria - Edokpa, Genesis D.; Uwagboe, Precious N.; Ehigiamusoe, Enoma (International Journal of Research in Medical Sciences, 2021)
Background: Some studies have demonstrated that football players may be at risk for clinically relevant increases in blood pressure (BP). BP is often associated with intraocular pressure (IOP). However, there is scarce literature on BP and IOP in football athletes. The aim of this investigation was therefore to study BP and IOP in young professional footballers and non-athletes. Methods: A cross-sectional study was conducted among nineteen (19) professional male football athletes of 18-28 years old; and nineteen (19) matched controls who were not active in any sports. All measurements were taken between 3 pm and 6 pm to lessen the effects of diurnal variations on IOP. Case history was first carried out to ascertain if the subjects were suitable for the study. Non-athletic subjects were matched with athletes according to sex, age, body mass index and random blood sugar. BP was measured in the right arm of each subject in sitting position with a mercury sphygmomanometer. IOP was measured in both eyes with a Schiotz tonometer. Results: Compared to non-athletes, the professional football athletes had significantly higher mean systolic BP (p=0.003), diastolic BP (p=0.030) and IOP (p=0.036). There was no correlation between IOP and systolic or diastolic BP in the football athletes (p>0.05). Conclusions: The young professional footballers were more predisposed to high blood pressure and ocular hypertension than the matched controls.